PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MEMBENTUK KARAKTER PADA SISWA KELAS XI SMA INTEGRAL HIDAYATULLAH BERAU - Ulfa Lailatun Nisrochah (JURNAL ILMIAH EDUNOMIKA, 2024)
This research aims to determine the role of Islamic religious education teachers in forming character in class XI students located at Hidayatullah Integral High School. In this research, we analyze the character of class. The research method used in this research is a descriptive qualitative method with data collection techniques through interviews, observations and interviews in order to describe phenomena in order to obtain information that is displayed in a key picture of the phenomenon, and obtain the desired research results. The object of study in this research is the XI students of Integral Hidayatullah High School, and the subject of this research is the Islamic Religious Education Teacher of Hidayatullah Integral High School. The results of this research are that the researcher revealed that the character of class XI students at Hidayatullah Integral High School in terms of religion and responsibility can be said to be good. Various efforts are made by the school in character building and instilling Islamic values through teaching and learning activities at the beginning of the semester, namely, annual activities, memorizing and muraja'ah Al-Qur'an, dhuha prayer activities, congregational prayers, lectures and activities evening prayer. The teacher's role in shaping the character of class XI students is by using various methods, namely exemplary methods, advice and discussion. Furthermore, the inhibiting factor in this research is the lack of awareness among students and parents about the importance of forming character and instilling Islamic values. The supporting factors in this research are the leadership of the school principal who understands the importance of good character according to Islam through the curriculum used, and the most important thing is the role of parents who participate in helping to build character according to Islamic values. Keywords: Role, Teacher and Character.